A model of an optimum currency area - Luca Antonio Ricci (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper develops a two-country model to investigate the circumstances under which it is beneficial to participate in a currency area. It captures both the real and monetary arguments suggested by the optimum currency area literature in a simple monetary model of trade with nominal rigidities. The net benefits that one country expects from participation in a currency union increase with: the correlation of real shocks between countries; the degree of international labor mobility; the degree of adjustment provided by a fiscal tool; the difference between the inflationary bias of the domestic authority and the inflationary bias of the authority of the currency union; the variability of domestic monetary shocks; the extent of the deadweight and efficiency gains deriving from the adoption of a single currency. The same net benefits decrease with: the variability of real shocks; the variability of foreign monetary shocks; and the correlation of monetary shocks between countries. The effect of the degree of openness on the net benefits is ambiguous. This last result contrasts with the usual argument that the more open economies are the better candidates they make for a currency area.
Keywords: 330; Optimaler Währungsraum; Außenwirtschaftstheorie; Internationale Arbeitsteilung; Offene Volkswirtschaft; Theorie